Desmopressin treatment for nocturia caused by nocturnal polyuria: practical guidelines - Przydacz, Mikolaj (Cent European J Urol, 2020)
INTRODUCTION: Desmopressin is an effective and safe therapy for nocturia caused by nocturnal polyuria. However, many physicians are unsure about the proper diagnosis of nocturnal polyuria and the identification of patients who may benefit from desmopressin treatment. Therefore, to support urologists in their routine clinical practice, the aim of this study was to provide a comprehensive paradigm for diagnosing nocturnal polyuria with recommendations for the use of desmopressin. MATERIAL AND METHODS: A multidisciplinary group of experts reviewed the available literature. Findings were compiled into a practice-based approach for workup and treatment. RESULTS: We designed the nocturia diagnostic pathway to confirm nocturnal polyuria, identify possible causes of nocturnal polyuria, and classify patients with indications and contraindications for desmopressin therapy. A bladder diary remains a basic diagnostic tool. Underlying conditions that may lead to nocturnal polyuria include mainly cardiac insufficiency, arterial hypertension, chronic kidney failure, obstructive sleep apnea, peripheral edema, and excessive fluid intake at night. Treatment for nocturia caused by nocturnal polyuria is based on conservative management and pharmacotherapy, but pharmacological treatment should not precede a prior attempt at conservative treatment. Before administration of desmopressin, patients should be assessed for serum sodium concentration and carefully educated about the symptoms of hyponatremia. Older individuals or persons with risk factors for the development of hyponatremia should be checked regularly for hyponatremia during desmopressin therapy. CONCLUSIONS: People with nocturia due to nocturnal polyuria should be evaluated carefully before initiating desmopressin treatment. Patients treated with desmopressin should be followed for both clinical efficacy and treatment-related adverse effects.